2014
DOI: 10.1167/iovs.13-13567
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing in Thai Patients With Retinitis Pigmentosa Reveals Novel Mutations in Six Genes

Abstract: This is the first report of mutations in Thai RP patients. These findings are useful for genotype-phenotype comparisons among different ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
5
46
1
Order By: Relevance
“…14,15 In 2012, Estrada-Cuzcano and colleagues characterized the C8orf37 gene and identified C8orf37 mutations by searching a region of chromosome 8 linked to patients with autosomal recessive early to adolescent-onset retinal dystrophies (arRP and arCRD) in four families. 14 Subsequently, the same group (van Huet and co-authors) reported the patients' clinical features in the four families, revealing that the disease progression rate was high in all patients with C8orf37 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15 In 2012, Estrada-Cuzcano and colleagues characterized the C8orf37 gene and identified C8orf37 mutations by searching a region of chromosome 8 linked to patients with autosomal recessive early to adolescent-onset retinal dystrophies (arRP and arCRD) in four families. 14 Subsequently, the same group (van Huet and co-authors) reported the patients' clinical features in the four families, revealing that the disease progression rate was high in all patients with C8orf37 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…16 Another group also showed an adolescent-onset RP phenotype with macular atrophy caused by C8orf37 mutations in one family. 15 The phenotypic characteristics of C8orf37 mutations are severely constricted visual fields, retinal degeneration with macular atrophy, and non-recordable responses in both rod and cone ERG. 16 Thus, the ophthalmic findings resulting from C8orf37 mutations are similar between patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been only six previous reports describing C8orf37 mutations, 1,2,[5][6][7][8] and no clear genotype-phenotype correlations have been described so far. The present study examined a consanguineous family of Moroccan origin including two siblings with early-onset CRD.…”
Section: Introductionmentioning
confidence: 99%